Governors, Politics and The Colonial Office : Public Policy in Hong Kong, 1918?8 - Ure, Gavin (Royal Asiatic Society Hong Kong studies series., 2012)
This book fleshes out the impact of political figures and how their actions, and inactions, affect various imperial or Hong Kong political and administrative affairs. The tendrils of Hong Kong's budding autonomy from the United Kingdom are identified and followed with attention paid to the various actors, including observing which actors fade in importance and which ones seize more of the stage.